Pengaruh Kegiatan 2m (Menggambar & Menempel Terhadap Perkembangan Seni Rupa Anak Usia 5-6 Tahun Di TK Bakti Pertiwi Desa Batang Pane II Padang Lawas Utara Sumatera Utara - Tanti Rahayu; Dewi Sri Suryanti; Nurhayati (Kilau Publishing, 2026)
This study was motivated by the limited implementation of visual art activities in early childhood education that effectively support children's artistic development. Learning activities tend to be less varied, providing children with insufficient opportunities to develop their drawing and collage skills optimally. This study aimed to determine the effect of the 2M activities (Drawing and Pasting) on the visual art development of children aged 5–6 years at TK Bakti Pertiwi, Batang Pane II Village, North Padang Lawas, North Sumatra. The study employed a quantitative approach using a one-group pretest–posttest experimental design. The research population consisted of 25 children, while the sample included 14 children from Group B selected through purposive sampling. Data were collected through observation, tests, and documentation and were analyzed using the t-test to examine the research hypothesis. The findings revealed that the 2M activities had a significant positive effect on children's visual art development. The average visual art development score increased from 28.27% in the pretest to 92.26% after the treatment (posttest). Furthermore, the t-test results showed that the calculated t-value (13.803) was higher than the t-table value (1.782), with a significance value of 0.000 < 0.05. Therefore, the null hypothesis (H₀) was rejected, and the alternative hypothesis (H₁) was accepted. It can be concluded that the 2M activities (Drawing and Pasting) significantly improve the visual art development of children aged 5–6 years at TK Bakti Pertiwi. These activities can therefore be implemented as an effective learning strategy to foster creativity and artistic skills in early childhood education